Effects of Ozone on Leaf Senescence, Photochemical Efficiency and Grain Yield in Two Winter Wheat Cultivars. Issue 4 (21st December 2012) - Burkart, S.; Bender, J.; Tarkotta, B.; Faust, S.; Castagna, A.; Ranieri, A.; Weigel, H.‐J.
Abstract The adverse effects of tropospheric ozone (O3) on crop photosynthesis, growth and yield have been documented in numerous studies over the last decades, but little information from field experimentation exists on how modern European winter wheat cultivars respond to O3. Two winter wheat cultivars (Astron and Pegassos) differing in development characteristics were exposed to non‐filtered ambient air or non‐filtered air plus 30 ppb and non‐filtered air plus 60 ppb O3 (8 h day−1) in open‐top field chambers. At several dates during growth, green leaf area was determined by destructive harvests. Leaf gas exchange, pigment content and xanthophyll cycle activity, and photochemical efficiency by chlorophyll a fluorescence were measured. O3 exposure induced accelerated senescence with no difference between cultivars. Photosynthesis declined especially in Pegassos; however, stomatal conductance was hardly affected by O3. Pigment contents were reduced by O3 exposure, and de‐epoxidation index increased. Photochemical efficiency (Fv/Fm) declined, whereas actual quantum yield (ΦPSII) did not respond to O3. O3 exposure reduced grain yield in both cultivars. However, yield of Pegassos was more affected by O3 exposure than yield of Astron, suggesting a higher O3 sensitivity of Pegassos. The data presented in this manuscript indicate a need to test whether high‐yield varieties such as Pegassos are particularly sensitive to O3 exposure.